Exploring Strategic Management Elements that Influence Productivity in the Manufacturing Industry - Abdullah, Nur Syamimi; Kahirol Mohd Salleh (Research and Innovation in Technical and Vocational Education and Training, 2025)
This paper explores the strategic management elements influencing productivity within Malaysia’s automotive manufacturing sector, focusing on a case study of Proton Holdings Berhad in Tanjung Malim. Through a qualitative case study approach involving two senior managers from the Human Resources and Operations departments, this study uncovers how strategic goal setting, human capital development, technological integration, and structured communication enhance organizational productivity. The findings are analyzed in light of Total Quality Management (TQM) principles, particularly Kaizen, PDCA cycles, and continuous improvement culture. The study reveals that effective integration of strategic elements improves decision-making, fosters innovation, and builds a proactive organizational culture. This research contributes to a deeper understanding of practical strategic implementation within automotive firms and provides policy insights for national industrial advancement